Kinematic Calibration of Super-Length Journey Parallel Robots for Spacecraft Docking Motion Simulation Platform - Yu, Dayong (Recent Patents on Mechanical Engineering, 2017)
Background: The 6-DOF super-length journey parallel robot is one of the most important equipments in the spacecraft docking motion simulation platform, and the simulation precision of the spacecraft docking motion simulation platform is determined by the 6-DOF super-length journey parallel robot’s pose accuracy. The pose error exits unavoidably because of the effect of kinematic parameter errors on the pose. Objective: In order to improve the 6-DOF super-length journey parallel robot’s pose accuracy, a kinematic calibration method considering all kinematic parts that have an influence on pose accuracy is presented in this paper. Methods: A kinematic calibration model is established through the inverse kinematics and vector differential theory. The correctness and rationality of the kinematic calibration model are verified by number simulation. The kinematic parameter errors are measured and estimated by 3-D coordinate measuring machine and least square algorithm. A measurement method is developed to measure the pose of the 6-DOF super-length journey parallel robot, which mainly measures the nine lengths from three reference points on the end-effector to three reference points on the base by 3-D coordinate measuring machine, after that calculates the 6-DOF super-length journey parallel robot’s pose by the lengths. Results: The simulation and experimental results are presented to demonstrate that the kinematic calibration and pose accuracy compensation method can decrease the pose error of the 6-DOF super-length journey parallel robot. Conclusion: The kinematic calibration technology has improved pose accuracy of the 6-DOF superlength journey parallel robot built in Aerospace System Engineering Shanghai. In this article, we have discussed some recent patent on error modeling and kinematic calibration of parallel robots.
Keywords: simulation accuracy